The impact of between‐session habituation, within‐session habituation, and weight gain on response to food exposure for adolescents with eating disorders. Issue 3 (10th January 2023) - Essayli, Jamal H.; Forrest, Lauren N.; Zickgraf, Hana F.; Stefano, Emily C.; Keller, Kathleen L.; Lane‐Loney, Susan E.
Abstract: Objective: Exposure therapy is a promising treatment for eating disorders (EDs). However, questions remain about the effectiveness of exposure to feared foods during the weight restoration phase of treatment, and the importance of between‐session and within‐session habituation. Method: We recruited 54 adolescents from a partial hospitalization program (PHP) for EDs which included daily food exposure. Throughout treatment, participants provided subjective units of distress (SUDS) ratings before and after eating a feared food, and completed measures of ED symptomatology. Results: Multilevel models found that pre‐exposure SUDS decreased over time, providing some evidence that between‐session habituation occurred. In contrast, the difference between pre‐exposure and post‐exposure SUDS did not decrease over time, indicating that within‐session habituation did not occur. Weight gain predicted greater between‐session habituation to feared foods, but did not predict within‐session habituation. Between‐session habituation, but not within‐session habituation, predicted favorable treatment outcomes, including weight gain and improvements on the Children's Eating Attitudes Test and Fear of Food Measure. Discussion: Partial hospitalization programs that include daily exposure to feared foods may be effective at decreasing anxiety about foods for adolescents with EDs who are experiencing weight restoration. Further research is warranted to replicate our findings challenging the importance of within‐session habituation, and to better understand between‐session habituation and inhibitory learning as mechanisms of change when conducting food exposure for EDs. Public Significance: This study provides some evidence that PHPs that include food exposure may be useful for adolescents with EDs who are experiencing weight restoration. Between‐session habituation, but not within‐session habituation, predicted favorable treatment outcomes. Further research is needed to determine whether clinicians can disregard within‐session habituation when conducting food exposure for EDs, and understand the importance of between‐session habituation as a potential mechanism of food exposure.